A Comparison of Pregabalin and Ketamine in Acute Pain Management After Laparoscopic Cholecystectomy - BİLGİLİ, BELİZ; ZENGİN, SENİYYE ÜLGEN (AVES, 2018)
Objective: Pregabalin and ketamine are popular analgesic adjuvants for improving perioperative pain management. We designated this double-blind, placebo controlled study to test and compare the preventive effects of pregabalin and ketamine on postoperative pain management after elective laparoscopic cholecystectomy. Methods: Seventy five patients (18 to 65 years of age) undergoing laparoscopic cholecystectomy were randomly assigned to one of the following 3 groups: control group (group C) received oral placebo capsule 1 h before surgery and bolus plus intravenous (iv) infusion of saline during surgery; ketamine group (group K) received oral placebo capsule 1 h before surgery and 0.3 mg kg(-1) iv bolus plus 0.05 mg kg(-1) h(-1) iv infusion of ketamine during the surgery; pregabalin group (group P) received oral pregabalin 150 mg 1 h before surgery and bolus plus iv infusion of saline during surgery. The anesthetic technique was standardized, total tramadol consumption, visual analog scale (VAS), incidence of postoperative nausea and vomiting (PONV), sedation score and complications related to the drugs used in the study were assessed in the postoperative 24 h period. Results: Postoperative total tramadol consumption were significantly lower in the pregabalin and ketamine group compared to the group C (p=0.001). Tramadol requirement was similar between pregabalin and ketamine groups. At 30 min postoperatively, VAS values were lower in the pregabalin and ketamine groups compared with group C (p=0.001). There was no difference between the three groups in the need for supplemental analgesia, incidence of PONV and sedation score >2. Discussion: Pregabalin and ketamine improved postoperative pain control and decreased analgesic consumption after laparoscopic cholecystectomy with a good safety profile without any changes in sedation level or PONV.
Keywords: Postoperative pain; pregabalin; ketamine; laparoscopic cholecystectomy; RANDOMIZED-CONTROLLED-TRIAL; IMMEDIATE POSTOPERATIVE PERIOD; MAJOR ABDOMINAL-SURGERY; LOW-DOSE KETAMINE; MORPHINE CONSUMPTION; CESAREAN DELIVERY; ANALGESIA; HYSTERECTOMY; BUPIVACAINE; GABAPENTIN